Determination of gaseous and particulate emission factors from road transport in a Middle Eastern capital. (June 2020) - Abdallah, C.; Afif, C.; Sauvage, S.; Borbon, A.; Salameh, T.; Kfoury, A.; Leonardis, T.; Karam, C.; Formenti, P.; Doussin, J.F.; Locoge, N.; Sartelet, K.
Highlights: First study in the Middle East reporting detailed road transport emission factors. High emission factors for PM2.5 and VOC compared to other regions. High emission factors in Lebanon compared to some developed countries end of 1990s. Major increase of emission factors due to local practices. Abstract: Road transport is a major source of anthropogenic emissions especially in the Middle East where the regulations enforcement is generally poor. This study aims to quantify the Emission Factors (EF) of traffic-related gaseous and particulate pollutants inside the Salim Slam urban tunnel in Beirut, Lebanon. The fuel-based emission factors of measured pollutants were from the carbon mass balance model. The EF determined showed general higher values than those reported in recent studies from European and American countries, even for speciated NMVOC. The average CO and NOx emission factors for the mixed fleet (HDV + LDV) were determined to be 10.52 ± 3.00 g km −1 and 2.20 ± 0.57 g km −1 respectively, while the EF for PM2.5 55 ± 27 mg km −1 . Moreover, IVOC species from gaseous phase were reported for the first time in the region. A reduction trend was observed in comparison with the previous tunnel study from Lebanon, however there is still a need to have tougher regulations to control the local practices such as removal of catalytic converter, adjustment of engine parameters for inspection, etc. The comparison of the EF to those calculated through EMEP or IPCC methodologies shows the need to take local practices while establishing national emission inventories.